Randomized self-updating process for clustering large-scale data - Shiu, Shang-Ying; Chin, Yen-Shiu; Lin, Szu-Han; Chen, Ting-Li (Statistics and computing, 2024)
This paper introduces the randomized self-updating process (rSUP) algorithm for clustering large-scale data. rSUP is an extension of the self-updating process (SUP) algorithm, which has shown effectiveness in clustering data with characteristics such as noise, varying cluster shapes and sizes, and numerous clusters. However, SUP’s reliance on pairwise dissimilarities between data points makes it computationally inefficient for large-scale data. To address this challenge, rSUP performs location updates within randomly generated data subsets at each iteration. The Law of Large Numbers guarantees that the clustering results of rSUP converge to those of the original SUP as the partition size grows. This paper demonstrates the effectiveness and computational efficiency of rSUP in large-scale data clustering through simulations and real datasets.